Letter from Daniel D.L. Farson to Margaret M. Booth, July 8, 1888 - Farson, Daniel D. L. (1888)
Pennsylvania Horticultural Society Secretary, Daniel D. L. Farson writes to Margaret M. Booth to express the Society's reaction to her late husband's death.
Keywords: Booth, James Curtis, 1810-1888; Pennsylvania Horticultural Society; Martinez Cardeza, Margaret